Challenges in Transforming Assessments for 21st Century Skills Development: Lecturers’ Perspective - Murugiah, Thiruchelvi K (Asian Journal of Education and Training, 2020)
The primary purpose of an assessment in pedagogy is to provide data and revise planned instructions. As the producers of skilled labour for the private sector, private higher education institutions (PHEIs), need to facilitate the transformation of assessments focused on developing 21st century skills competencies in students. In preparing for Industry 4.0, the private sector in Malaysia is concerned about fresh graduates not being adequately skilled for the workplace. The gap can lead to unemployment and a shortage in skilled labour. This research is designed to understand the challenges in transforming assessments to address the 21st century skills gap. Based on an epistemological belief through a social constructivist interpretive framework, a case study approach is used to co-construct the reality shaped by the course lecturers’ experiences. Based on purposeful sampling, two (2) business lecturers with over five (5) years of teaching experience, and familiar with the diploma standards were selected from the School of Business. Data was collected using semi-structured interviews, document reviews and audiovisual materials. A data analysis strategy of reducing codes to themes and identifying patterned regularities was used to produce a written report. The findings reveal the challenges faced by lecturers in transforming assessments to develop 21st century skills. The recommendation is for assessments to be transformed based on private sector skill needs to keep up with the changing work skills demands of Industry 4.0. Continuous initiatives in shared value partnerships with the private sector will ensure that the development of 21CS remains relevant.